PENGHINDARAN PAJAK DILIHAT DARI SISI TRANSFER PRICING, RETURN ON ASSET, DAN UKURAN PERUSAHAAN : TAX AVOIDANCE VIEWED FROM THE PERSPECTIVE OF TRANSFER PRICING, RETURN ON ASSETS, AND FIRM SIZE - Suhermanto, Putri Amanda; Mardjono, Enny Susilowati (Universitas Riau, 2025)
This study aims to examine the impact of transfer pricing, Return on Assets (ROA), and firm size on tax avoidance. The research utilizes data from energy sector companies listed on the Indonesia Stock Exchange during period of 2019-2023 period, with a total of 103 observations obtained through purposive sampling. Hypotheses were tested using regression analysis with SPSS 25. The results indicate that transfer pricing and ROA do not influence tax avoidance, while firm size has an affect tax avoidance. Based on this study, the government should pay attention to the size of companies in efforts to address tax avoidance. Thus, tax authorities can formulate more effective policies to reduce such practices and enhance tax compliance.